Estudio comparativo del rendimiento de los servidores web IIS y APACHE. - Yunapanta Tiama, Gilson Euclides (2023)
This case study work was carried out with the purpose of carrying out a comparative study between ISS and APACHE web servers. Where it is necessary to evaluate the requirements, the performance of web servers is highly variable due to different configurations, web servers are programmed to have the highest possible levels of performance, whose methodology was descriptive whose purpose is to describe these two servers of this type Research is used to collect information and data that describe a specific event, situation, or group of people. Mixed design was also applied as both qualitative and quantitative methods will be used where the former is used to provide a detailed and comprehensive understanding of the research topic. The population in this work is 802 and through the statistical formula the result was 260 people to survey, three questions were applied to know the way of using ISS and APACHE from the point of view of the students. Comparisons of the advantages and disadvantages of the two web servers were made, measured in terms of response time, performance and availability, response time refers to the time it takes for the server to respond to a request from a user.